Institutional Analysis of Shadow Economy (Study on ASEAN 7 Developing Countries) - Wibowo, Ana Rahmawati; Indrayanti, Wiwin (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the institutional variables of governance in ASEAN 7 developing countries. The independent variables consist of Voice and Accountability, Political Stability and Absence of Violence, Government Effectiveness, Regulatory Quality, Rule of Law and Control of Corruption, while shadow economy is dependent variable. The data used in this study are quantitative data and secondary data by using program Stata 14, the analysis technique used is multiple linear regression panel data. The results show that Voice and accountability has a negative and significant effect on the shadow economy as well as Political stability, Government effectiveness and Control of corruption on the other side. Regulatory quality has a positive and significant effect on the amount of shadow economy. Meanwhile, Rule of law no significant effect on the shadow economy. Underlying the results, the study arranges some policy to reduce negative effect of shadow economy.